Shaping E-commerce Experiences: Unraveling the Impact of Service Quality on Youth Customer Behavior in a Developing Nation - Muhammad Umair Wattoo; Jianguo Du; Fakhar Shahzad; Shakila Kousar (SAGE Open)
Firms of all stripes recognize that retaining satisfied customers in the current e-commerce cutthroat and digital market relies on delivering exceptional customer service. This longitudinal study aims to examine the relationship between service quality, customer satisfaction, and behavior in an online shopping environment, emphasizing the youth of Pakistan. A research model was developed and tested using two phases of customer data ( n  = 331). The results show that in the online shopping environment, the dimension of service quality significantly enhances customer satisfaction, which leads to the development of customer loyalty. The mediating role of customer complaints has been identified in the relationship between customer satisfaction and customer loyalty. Furthermore, it was found that the significant connection between customer loyalty, repurchase intention, and recommendation intention was moderated by emotional intensity. The findings will help firms in Pakistan and other developing countries to establish long-term growth strategies by understanding the complex nexus between service quality that leads to customer satisfaction and boosts their repurchases and recommendations. This research also directs online platform marketers and practitioners to develop marketing and retailing strategies.